Defining the Scope of Public Engagement: Examining the "Right Not to Know" in Public Health Genomics. (28th April 2014) - Allen, Clarissa; Sénécal, Karine; Avard, Denise
Abstract : In this article, we explore the concept of a "right not to know" on a population rather than individual level. We argue that a population level "right not to know" is a useful concept for helping to define the appropriate boundaries of public engagement initiatives in the emerging public health genomics context.